2008
DOI: 10.1590/s0066-782x2008001700003
|View full text |Cite
|
Sign up to set email alerts
|

Redução da pressão arterial e do duplo produto de repouso após treinamento resistido em idosas hipertensas

Abstract: SummaryBackground: Due to the existing controversies in literature about the potential benefits of resistance exercise training (RT) on arterial blood pressure (BP) at rest, and the lack of studies conducted with elderly hypertensive individuals, RT is seldom recommended as a non-pharmacological treatment for arterial hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
30
1
20

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 29 publications
6
30
1
20
Order By: Relevance
“…Our findings corroborate previous studies involving resistance training and BP control, in which reduction in DBP 20,21 and in MBP 15,22 was also verified. On the other hand, some studies did not observe reduction in DBP after intervention with resistance training 23,24 .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our findings corroborate previous studies involving resistance training and BP control, in which reduction in DBP 20,21 and in MBP 15,22 was also verified. On the other hand, some studies did not observe reduction in DBP after intervention with resistance training 23,24 .…”
Section: Discussionsupporting
confidence: 92%
“…Concerning reduction in SBP at rest, our results are similar to the ones in many studies [23][24][25][26] , which did not verify hypotensive effect after resistance training in SBP either. Nevertheless, such reduction was verified in other studies 15,20,[27][28][29] . Regarding magnitude of BP reduction, it was verified that in both groups of the present study this reduction was more remarkable than in the values found in previous investigations conducted specifically with an elderly population 15,20,23,27 .…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations